1988
DOI: 10.1002/art.1780310220
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative spondylolisthesis, synovial cyst of the zygapophyseal joints, and sciatic syndrome: report of two cases and review of the literature

Abstract: Two cases of sciatica secondary to nerve root compression by a "synovial cyst" of a zygapophyseal joint are described. In light of these 2 cases and on reviewing the literature, it appears that zygapophyseal joint osteoarthritis with degenerative (or articular) spondylolisthesis can be a predisposing factor to the formation of such synovial expansions and, consequently, the cause of nerve root compression. The coexistence of a lumbar degenerative spondylolisthesis with a radicular syndrome should therefore enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 20 publications
0
26
0
1
Order By: Relevance
“…7 c). Acute onset sciatica can be due to acute haemorrhage into the LFSC [17,20]. In this situation MR imaging may show evidence of subacute breakdown products of blood within the LFSC (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 c). Acute onset sciatica can be due to acute haemorrhage into the LFSC [17,20]. In this situation MR imaging may show evidence of subacute breakdown products of blood within the LFSC (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous resolution also occurs (Fig. 7 d) [38], and cyst rupture has been cited as an explanation for this [1,17,49]. Conversely, progressive symptoms have been described in association with increasing cyst size [18,54].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported that LSCs may occur in association with trauma, 3) rheumatoid arthritis, 29) and degenerative disorders of the spine in older individuals, 13) contributing to attendant degenerative spondylolisthesis. 33) LSCs may project from the anterior or posterior aspect of the facet joints, protruding internal or external, respectively, to the spinal canal, 19) and diameter may range between 3 to 30 mm. 35) Accordingly, some surveys on their prevalence, based on computed tomography (CT) or magnetic resonance (MR) imaging of the lumbar spine in a symptomatic population, revealed that LSCs are responsible for neurological complaints only in …”
Section: Introductionmentioning
confidence: 99%